Women’s vulnerability to STIs and HIV transmission: high risk sexual behaviour in Denpasar City - Desak Made Sintha Kurnia Dewi; Luh Putu Lila Wulandari; I Nyoman Mangku Karmaya (Universitas Udayana, 2013)
Department of Health of Bali Province reported an increase of reported HIV cases among pregnant women. A sero-survey among pregnant women in 2010 has found 1% of pregnant women are HIV positive. This fact might indicate the possibility of women’s vulnerability to HIV in Bali, mainly due to the high risk behavior of their sexual partner. There has been limited study exploring this vulnerability, and how this vulnerability might affect their risk in contracting HIV. This study aimed at exploring women’s vulnerability to HIV by looking at the individual, households and their community high risk behaviors which might consequently affect the women risk to HIV transmission. Qualitative study was employed by using indepth semi structured interview with 21 informants. The informants were chosen to ensure the variations of the risk behaviors as such might reveal different risk which might affect women. The informants consisted of men, women, HIV counselor and health providers in three different health services in Denpasar. Data was analysed using thematic analysis. To improve data validity, member checking and peer debriefing techniques were used. The study found that there has been variation in the factors which affects women’s vulnerability within individual, household, and community levels. These included the multisexual partners of women and or their sexual partners, buying sex, drug injecting behaviours of their partners and inconsistent condom use which due mainly to the low bargaining position of women in condom negotiation.